Design and implementation of a smart mobile phone jammer - Chebil, Jalel; Islam, Md. Rafiqul; Khan, Sheroz; Khalifa, Othman Omran; Ahmed, Musse Mohamud (s.n, 2012)
Intelligent mobile phone jammer is a device used to jam unathorized cellular phone while permitting authorized cellular phone to operate and control the usage of mobile phone in specific environment.